2024
DOI: 10.1038/s41467-023-44378-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing the critical nucleus size in tetrahydrofuran clathrate hydrate formation using surface-anchored nanoparticles

Han Xue,
Linhai Li,
Yiqun Wang
et al.

Abstract: Controlling the formation of clathrate hydrates is crucial for advancing hydrate-based technologies. However, the microscopic mechanism underlying clathrate hydrate formation through nucleation remains poorly elucidated. Specifically, the critical nucleus, theorized as a pivotal step in nucleation, lacks empirical validation. Here, we report uniform nanoparticles, e.g., graphene oxide (GO) nanosheets and gold or silver nanocubes with controlled sizes, as nanoprobes to experimentally measure the size of the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Sun et al reported that nonanoic acid with THF + water emulsion formed small crystal particles, eventually decreasing the induction time. Xue et al reported that the size of the nanoparticles could influence the size of the critical nucleus required for hydrate formation. The aluminum hydroxide formation requires the addition of a base to let pH fall in the specified range.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al reported that nonanoic acid with THF + water emulsion formed small crystal particles, eventually decreasing the induction time. Xue et al reported that the size of the nanoparticles could influence the size of the critical nucleus required for hydrate formation. The aluminum hydroxide formation requires the addition of a base to let pH fall in the specified range.…”
Section: Resultsmentioning
confidence: 99%